Heat-induced interactions of [beta]-lactoglobulin, [alpha]-lactalbumin and casein micelles : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Education in Food Technology at Massey University - Chiweshe, Martha Chogugudza (Massey University, 1996)
The denaturation and aggregation of β-lactoglobulin and α-lactalbumin were studied in the following mixtures, designed to simulate the protein concentrations and ionic environment in normal skim milk. 1. β-lactoglobulin (0.4% w/v), 2. α-lactalbumin (0.15% w/v), 3. β-lactoglobulin (0.4% w/v) and casein micelles (~ 2.6% w/v), 4. α-lactalbumin (0.15% w/v) and casein micelles (~ 2.6% w/v), 5. β-lactoglobulin (0.4% w/v) and α-lactalbumin (0.15% w/v) and 6. β-lactoglobulin (0.4% w/v), α-lactalbumin (0.15% w/v) and casein micelles (~ 2.6% w/v) Proteins were dissolved in SMUF, pH 6.7, and heated at 80 and 95°C for various times and centrifuged at 100,000 g for 60 min. The supernatants and pellets obtained were analysed using gel electrophoresis under non-dissociating (Native-PAGE in the absence of dissociating and reducing agents), dissociating but non-reducing (SDSNR-PAGE) and dissociating and reducing conditions (SDSR-PAGE). When β-lactoglobulin was heated alone and examined by native-PAGE, the quantity of native protein decreased with increasing heating time at 80°C. Addition of α-lactalbumin to the β-lactoglobulin solution increased the loss of β-lactoglobulin during the initial stages of heating. Addition of casein micelles to the β-lactoglobulin solution markedly increased the loss of native β-lactoglobulin throughout the heating period. The loss of β-lactoglobulin from the mixture containing β-lactoglobulin, α-lactalbumin and casein micelles was similar to that from the mixture of β-lactoglobulin and casein micelles. The loss of β-lactoglobulin from these protein mixtures could be described by second-order reaction kinetics. Heating these mixtures at 95°C caused very rapid loss of native β-lactoglobulin, but the effects of the addition of casein micelles and α-lactalbumin were generally similar to those observed at 80°C. When α-lactalbumin was heated at 80°C either alone or in the presence of casein micelles, there was only a slight loss of the native α-lactalbumin. However the corresponding losses of native α-lactalbumin were considerable greater on heating at 95°C. At both temperatures, the addition of β-lactoglobulin increased the rate of loss of α-lactalbumin substantially. The addition of casein micelles to the mixture of α-lactalbumin and β-lactoglobulin had little further effect on the loss of native α-lactalbumin. The rates of loss of α-lactalbumin at 95°C in all mixtures could be adequately described by first-order kinetics. When β-lactoglobulin was heated either alone or in the presence of casein micelles and examined by SDSNR-PAGE, the loss of SDS-monomeric β-lactoglobulin was less than the loss of native β-lactoglobulin. In contrast, when α-lactalbumin was added to β-lactoglobulin or β-lactoglobulin and casein micelles mixture, the loss of SDS-monomeric β-lactoglobulin was comparable to that of native β-lactoglobulin. The difference between native and SDS-monomeric β-lactoglobulin represents aggregates that are linked by non-covalent (hydrophobic) interactions. Thus the protein mixtures containing α-lactalbumin, contain no or little non-covalently linked β-lactoglobulin aggregates, and consequently, all the β-lactoglobulin aggregates would be disulphide linked. The results for the loss of SDS-monomeric and native α-lactalbumin at 95°C showed that both non-covalent and disulphide-linked aggregates of α-lactalbumin were present in all the protein mixtures studied. When β-lactoglobulin solution was heated at 95°C, large aggregates were formed which could be sedimented at 100,000 g for 60 min. Addition of casein micelles to β-lactoglobulin solution caused greater sedimentation of β-lactoglobulin. Similar results were obtained when the mixture containing β-lactoglobulin, α-lactalbumin and casein micelles was heated at 95°C. In contrast, the mixture containing β-lactoglobulin and α-lactalbumin behaved in a similar manner to β-lactoglobulin alone. When α-lactalbumin was heated at 95°C alone or in the presence of casein micelles, it did not interact to form large sedimentable aggregates. However when β-lactoglobulin was added to the above protein solutions, there was a considerable increase in sedimentation of α-lactalbumin.
Keywords: Whey; Protein denaturation; [beta]-lactoglobulin; Skim milk; Casein